A Comparative Study of Impedance Measurement Techniques for Structural Health Monitoring Applications - Budoya, Danilo Ecidir [UNESP]; Baptista, Fabricio Guimarães [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Structural health monitoring (SHM) systems are scientifically and economically relevant as methods of detecting structural damage to various types of structures, thus increasing safety and reducing maintenance costs. Among the various principles of damage detection, the electromechanical impedance (EMI) method is based on the electrical impedance measurement of piezoelectric transducers attached to the monitored structure. Here, the accuracy and precision of the measurement system are fundamental for the correct diagnosis of the structure. Therefore, this paper performs a comparative analysis of two impedance measurement techniques for damage detection that are typically used in commercial impedance analyzers and other alternative measurement systems: 1) transient-state measurements using a sweep excitation signal and 2) steady-state measurements using a pure sinusoidal signal for each excitation frequency. Tests were performed with resistive and capacitive loads with known values and a piezoelectric transducer fixed to an aluminum bar representing a monitored structure. The two techniques were compared based on the accuracy, precision, and time required for the measurements. The results highlight the important features of each technique that should be considered for the development of impedance-based SHM systems and the correct diagnosis of monitored structures.
Keywords: Electromechanical; impedance; measurement; piezoelectric transducers; structural health monitoring (SHM)